HISTOPATHOLOGY IN FORENSIC PRACTICE (Journal of Forensic Medicine & Toxicology, 2024)
Examination of tissues and cells for forensic purposes is very helpful in reaching to conclusion in forensic practice. The teaching of histopathology is almost negligible in postgraduate forensic medicine. Majority of forensic specialist in India and other neighboring country lack these skills. To help these practitioners and new postgraduates, a concept of modular teaching is being emphasized so their skills and knowledge can be upgraded. A basic module covering essential parts required in day to day practice of forensic are given in a very simple way. Some important issues are covered in this article aiming to develop it further in different other forms.
Keywords: forensic histopathology; microscopy in the help of justice; forensic histology